Kemandirian Ibu Postpartum Dalam Perawatan Bayi Baru Lahir dengan Menggunakan Pendekatan Model “Mother-Baby Care (M-BC)”: Postpartum Mother's Independence in Newborn Care Using the "Mother-Baby Care (M-BC)" Model Approach - Vetty Priscilla (NERS Jurnal Keperawatan, 2013)
Postpartum mothers need a special approach to take care her newborn especially primiparous. Mother - Baby Care ( M - BC ) model is an approach desain that aims to make postpartum mothers independently in performing newborn care. The purpose of this study is to see the effectiveness of a model M - BC in newborn care . The study design was using a quasi-experimental pretest - posttest with number of samples is 20 postpartum mothers . The results showed that the independence of postpartum mothers in newborn care have averaged 31.81 before the intervention and after the intervention was increased 5.91 toward 37.72. Wilcoxon test showed significant difference between the independence of postpartum mothers before and after the intervention where p = 0.024 ( p < 0.05 ) . It is suggested to health practitioners to use the Mother - Baby Care (M - BC ) model as one of the guidelines for the health education in order to increase independence of mother in caring of the newborns